2023
DOI: 10.1002/clen.202200396
|View full text |Cite
|
Sign up to set email alerts
|

Water hyacinth as a green and sustainable material for carbon aerogel electrodes utilized in membrane capacitive deionization

Abstract: Water hyacinth is a substantial and quick‐growing plant that can strongly invade and negatively affect the aquatic ecosystem, causing many problems to the water environment by consuming nutrients and oxygen from surface water. However, the hierarchical porous carbon derived from water hyacinth can be employed for the removal of oil spills, heavy metals, or wastewater nutrients. Recently, water‐hyacinth‐derived carbon aerogel has been utilized as electrode for the desalination of brackish water using membrane c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The aim behind the mapping of invasive species like water hyacinth is to facilitate the percentage area covered by the particular species for management. It is a well-known fact that water hyacinth is an extensive gregariously growing plant that can invade and impact the aquatic ecosystem, causing several problems to the water quality and its environment, also depleting nutrients and oxygen from surface water (Nguyen et al, 2023). Nguyen et al (2023) suggested that water hyacinth can be utilized for the removal of oil spills, heavy metals, or wastewater nutrients using the hierarchical porous carbon derived from water hyacinth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim behind the mapping of invasive species like water hyacinth is to facilitate the percentage area covered by the particular species for management. It is a well-known fact that water hyacinth is an extensive gregariously growing plant that can invade and impact the aquatic ecosystem, causing several problems to the water quality and its environment, also depleting nutrients and oxygen from surface water (Nguyen et al, 2023). Nguyen et al (2023) suggested that water hyacinth can be utilized for the removal of oil spills, heavy metals, or wastewater nutrients using the hierarchical porous carbon derived from water hyacinth.…”
Section: Discussionmentioning
confidence: 99%
“…It is a well-known fact that water hyacinth is an extensive gregariously growing plant that can invade and impact the aquatic ecosystem, causing several problems to the water quality and its environment, also depleting nutrients and oxygen from surface water (Nguyen et al, 2023). Nguyen et al (2023) suggested that water hyacinth can be utilized for the removal of oil spills, heavy metals, or wastewater nutrients using the hierarchical porous carbon derived from water hyacinth. Hence, strategic management plans and policies have been developed for the eradication of water hyacinth and the conservation of wetland.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, the most common and widely used material is AC 7 . However, the utilization of other types of carbonaceous materials, especially environmentally friendly ones (e.g., corn-stalk-based 8 , 9 and water hyacinth-based 10 carbon aerogels) as well as conventional ones (e.g., mesoporous carbon 11 , graphene 12 , and carbon nanotubes 13 ), the addition of metal oxide nanoparticles (e.g., TiO 2 14 , SiO 2 , Al 2 O 3 15 , and ZnO 16 ), and conductive polymers (e.g., polyaniline 17 and sulfonated polystyrene 18 ) to the carbonaceous structures of the electrodes were carried out to achieve a higher specific capacity, lower charge transfer resistance, more hydrophilicity, and better wettability. This leads to improved electrochemical performance in the CDI process 19 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, porous carbons derived from various biomass resources, such as corncob [16], corn straw [17], pomelo peel [18], celery [19] and rice straw [20] have been exploited for high-performance EDLC. Among them, carbon aerogel is one of carbon materials showing good electrochemical energy storage performance due to 3D hierarchical pores with tunable porous structure, high specific surface area and good conductivity, facilitating ions efficient diffusion in the carbon network [21][22][23].…”
Section: Introductionmentioning
confidence: 99%